Diagnostic dilemma in CNS Behçet's disease. (5th September 2012) - Ni Mhuircheartaigh, Orla; Hunt, Christopher; Huang, Josephine; Kumar, Neeraj; Matteson, Eric L
Abstract : A 23-year-old gentleman presented to the emergency department with new onset neurological dysfunction and painful oral and genital ulcers. Biopsies of the lesions noted non-specific inflammatory changes. MRI of the brain revealed a large mass-like lesion involving the pons, medulla, midbrain and surrounding cerebral tissue with T2 signal enhancement that was not amenable for biopsy. Both the ulcer biopsy results and the MRI findings could be attributed to either central nervous system (CNS) lymphoma or CNS Behçet's disease. A diagnosis of CNS Behçet's disease was thought to be most likely based on the clinical presentation and MRI findings. He was treated with high-dose immunosuppression and made a significant recovery.